Improving Students’ Green Energy Practical Skills Through Project-Based Industrial Electronics Learning for Sustainable Development Goals - Yunesman; Ambiyar; Hermasyah (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to improve students’ practical skills in green energy through the implementation of a Project-Based Learning (PjBL) model integrated with industrial electronics–based solar energy projects, supporting Sustainable Development Goals (SDGs) in higher education. The research employed a quantitative quasi-experimental design with a pre-test and post-test control group. Participants were second-semester Industrial Engineering students enrolled in an Industrial Electronics practicum course. The experimental group (n = 31) was taught using PjBL through the design and implementation of a microcontroller-based solar panel system, while the control group (n = 32) received conventional instruction. Data were collected using practical skill tests and performance observation rubrics. The results showed a substantial improvement in the experimental group, with the mean score increasing from 57.4 (pre-test) to 81.6 (post-test), whereas the control group showed a smaller increase from 56.9 to 65.3. Paired t-test analysis indicated a significant difference (p < 0.05), demonstrating the effectiveness of the PjBL model. These findings indicate that project-based industrial electronics learning effectively enhances students’ green energy practical skills. In conclusion, the study confirms that contextual PjBL can strengthen work-oriented competencies and support sustainable education aligned with SDGs.